Examining the influence of the internet and globalisation on politics, culture, and religion in contemporary muslim societies - Mohamed, Shafizan (Penerbit UiTM, 2025)
This article explores the relationship between the internet and globalisation, and how these two forces have significantly impacted contemporary Muslim societies. With the rise of technology and globalisation, there have been changes in politics, culture, and religion within Muslim societies. By examining cases in Muslim countries in the Middle East, Central Asia, and Southeast Asia, this article uncovers a complex blend of opportunities and challenges resulting from these dynamic interactions. The internet has provided a platform for discussions, cultural exchanges, and religious expressions among Muslims. However, it has also posed challenges by questioning authority and orthodoxy. Globalisation’s cultural diffusion has raised concerns about preserving identities amidst a flood of global influences. The formation of the Muslim Ummah as a community has been both facilitated by platforms that connect Muslims across borders, while also complicated by geopolitical tensions and ideological divisions that challenge unity, within the Ummah. This article emphasises the importance for Muslim societies to embrace the advantages of the new age while simultaneously addressing cultural and religious challenges to maintain unity within the Muslim Ummah. It is essential to comprehend the effects involved in order to navigate the changing dynamics of contemporary Muslim societies